JOB-DESK BASED TEXTBOOK FOR WORKING STUDENTS IN SPEAKING CLASS IN BATAM - Edel, Eky Erlanda (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2016)
The aim of this research is to identify the outlines of job-desk based speaking textbook for working students.By having this, it is expected that a decent job-desk textbook for working students who want to improve their performance at work in speaking area can be produced. Based on the conducted pre-research, it was found that the English Department worker students in Batam are charged with using English actively in presenting, introducing, explaining, discussing, negotiating, giving direction, and serving. Furthermore, based on those things above, the textbook used so far does not meet the needs of working students. Therefore, the researcher formulated a job-desk based textbook in speaking class to fulfill the working students’ needs specifically. This case study qualitative research on the students of English Department is conducted by applying purposive sampling technique. In addition, the data was collected through questionnaire and interview which were adjusted as the indicators of the textbook. The result showed that the students who work in Batam have problems in grammar, vocabularies, pronunciation and the language expressions in presenting, discussion, giving instruction and negotiating. Based on those problems, the researcher composed a textbook that could possibly solves the students’ problems at work.Keywords: Job-desk based textbook, Working students, Speaking